Perbedaan Motivasi dan Prestasi Belajar Siswa Kelas Unggulan dan Bukan Kelas Unggulan di SLTP - Musa Sukardi (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2000)
Motivation and Achievement Differences between Students of High-Achiever Group and Those of Non-High-Achiever Group. The purpose of this descriptive, comparative study was to find out the differences in learning motivation and achievement between students belonging to high-achiever group and those to non-high-achiever group. Forty one junior high school students of the former group and 40 of the latter were involved in this study. The data were obtained from a questionnaire and documentation study and analyzed using statistics of percentages and t-test. The results show that there is a significant difference between the two groups in terms of learning motivation and achievement.